2011
DOI: 10.1097/ncm.0b013e3181f508d0
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Perspectives of Heavily Comorbid Primary Care Adults

Abstract: Case managers have an opportunity to fill the gaps in care for patients with multiple comorbid conditions. The case manager has the potential to address several of the issues identified by the patients in this study by helping comorbid patients develop self-management skills and tailoring supportive primary care interventions to meet individual patient needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 18 publications
0
46
0
Order By: Relevance
“…2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage. 22 This study aims to better understand the health care utilisation and experiences of people with multimorbidity within the New Zealand health system, with a focus on where care is working well and where improvements could be made.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 People with multimorbidity face many health service challenges including: short consultation times and the requirement to arrange multiple appointments with different health care professionals; 9,10 poorly coordinated care and conflicting information from different health providers; [11][12][13][14][15][16] and difficulties accessing health care due to financial constraints, transport difficulties or limited understanding of the health care system. [17][18][19][20] New Zealand research is limited, but has found that multimorbidity has a considerable impact on people's lives 19,21 and is challenging for general practitioners (GPs) and practice nurses to manage. 22 This study aims to better understand the health care utilisation and experiences of people with multimorbidity within the New Zealand health system, with a focus on where care is working well and where improvements could be made.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 For example, though patients benefit from frequent follow-up, education about illness, coaching to support self-management, and access to community-based resources, physicians in primary care lack the time, tools, and resources to provide patients all these services. [7][8][9] Thus, the Institute of Medicine has urged redesign of chronic illness care delivery in primary care. 10 A widespread strategy for improving chronic illness treatment, [11][12][13][14][15][16][17] care management involves non-physician care managers working with patients between physician encounters to improve clinical care, enhance care coordination, [13][14][15] and reduce health care utilization.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other concerns of complex patients that may be addressed through general care management include making sense of information from multiple sources, prioritizing self-management strategies, navigating interactions with clinicians and systems, improving understanding of medications, and helping patients establish connections between different care recommendations. [14][15][16] The effectiveness of generalizing disease-specifi c interventions for patients with comorbidities to the broader population of patients with a range of multiple morbidities will depend on the outcomes assessed. For complex patients with symptomatic depression, it is unlikely that any health outcomes will improve without active management of the depression.…”
Section: Agency For Healthcare Research and Quality (Ahrq)mentioning
confidence: 99%